Digital-based Entrepreneurship Training to Realize Young Entrepreneurial Millennials - Alhusin*, Syahri; Widodo, Zandra Dwanita; Choerudin, Achmad; Zaelani, Abdullah; Wijastuti, Sri; Adiyani, Rini; Rahmalia, Vidia (Riwayat: Educational Journal of History and Humanities, 2023)
Being an entrepreneur is an attempt of activating Indonesian economic wheel. In the attempt of empowering creativity and innovation, the entrepreneurs are expected to grow into employers who can open job opportunities in various business sectors. This community service activity is entitled a digital-based entrepreneurship training to realize millennial generation with young entrepreneur spirit. This title was chosen based on the factual condition of people today characterized with the increased unemployment rate disproportional to the job opportunity availability. The problems encountered by participants are limited information and experience supporting the digital-based entrepreneurial activities, and limited knowledge on the detail of digital-based entrepreneurship, leading to the limited number of alumni and graduates choosing to be entrepreneurs. This activity aims to improve skill and to create digital-based young entrepreneurs to the participants in the partner location. The basic output with target to be achieved is the created independent business community having digital-based entrepreneurial skill. This community service was implemented in the form of entrepreneurship training and facilitation. The partner in this activity includes the students of Faculty of Business Economy of Universitas Tunas Pembangunan. Twenty participants participated in this activity. Evaluation was conducted using questionnaire distributed to the participants aiming to find out the students understanding on the implementation of training and interview. The result achieved in the end of community service activity is the improved understanding and skill of participants concerning digital-based entrepreneurship that can be indicated with the number of startups established by the participants.